Psychometric properties of the Dating Abuse Questionnaire in a sample of Mexican female students of middle and higher level. - Maricela Osorio-Guzmán (Instituto Nacional de Salud Pública, 2014)
Objective. The aim of the study was to modify and adapt the questionnaire Dating Abuse Italy-Mexico binational version (CMN) to a sample of female students of middle and higher level, from the Federal District and the State of Mexico. Materials and methods. Cross-sectional study. 2157 students participated, aged between 14 and 33 years old. The reagents were analyzed using item-scale method, and was applied a confirmatory factor analysis. Results. The CMN showed an internal consistency of α= 0.95, the Confirmatory factor analysis confirmed the five theoretical areas planned with satisfactory fit indices Conclusions. The psychometric characteristics of this version of CMN are adequate to reliably assess abuse in dating.